Management of yellow vein mosaic and leaf curl diseases of okra by adjusting date of sowing and row to row spacing - KALITA, M K; DHAWAN, P (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2001 and 2002 at ecs Haryana Agricultural university Hisar. Okra seeds were sown at 6 different dates starting from May to August at 4 different row-to-row spacing starting from 30 cm up to 75 em to see its effect on whitefly population build up, incidence YVMV and Lev diseases and yield of okra. Lowest whitefly population/plant, incidence of single and combined infections of YVMV and LeV were observed on early sown crop (May) at closer row-to-row spacing (30 cm) and highest on late sown crop (August) at wider spacing (75 em). Highest marketable yield of okra was obtained from okra crop sown in the frrst week ofJune at 45 em row-to-row spacing. Date ofsowing and row-to-row spacing ofokra can be adjuste4 to escape or reduce the disease incidence to get maximum yield.